UNIT 31.1 CRISPR/Cas9‐Directed Genome Editing of Cultured Cells. Issue 1 (1st July 2014) - Yang, Luhan; Yang, Joyce L.; Byrne, Susan; Pan, Joshua; Church, George M.
Abstract: Human genome engineering has been transformed by the introduction of the CRISPR (clustered regularly interspaced short palindromic repeats)/Cas (CRISPR‐associated) system found in most bacteria and archaea. Type II CRISPR/Cas systems have been engineered to induce RNA‐guided genome editing in human cells, where small RNAs function together with Cas9 nucleases for sequence‐specific cleavage of target sequences. Here we describe the protocol for Cas9‐mediated human genome engineering, including construct building and transfection methods necessary for delivering Cas9 and guide RNA (gRNA) into human‐induced pluripotent stem cells (hiPSCs) and HEK293 cells. Following genome editing, we also describe methods to assess genome editing efficiency using next‐generation sequencing and isolate monoclonal hiPSCs with the desired modifications for downstream applications. Curr. Protoc. Mol. Biol . 107:31.1.1‐31.1.17. © 2014 by John Wiley & Sons, Inc.